Fine Root Abundance and Dynamics of Stone Pine (Pinus cembra) at the Alpine Treeline Is Not Impaired by Self-shading - Kubisch, Petra; Leuschner, Christoph; Coners, Heinz; Gruber, Andreas; Hertel, Dietrich (Frontiers in Plant Science, 2017)
Low temperatures are crucial for the formation of the alpine treeline worldwide. Since soil temperature in the shade of tree canopies is lower than in open sites, it was assumed that self-shading may impair the trees' root growth performance. While experiments with tree saplings demonstrate root growth impairment at soil temperatures below 5-7 °C, field studies exploring the soil temperature – root growth relationship at the treeline are missing. We recorded soil temperature and fine root abundance and dynamics in shaded and sun-exposed areas under canopies of isolated Pinus cembra trees at the alpine treeline. In contrast to the mentioned assumption, we found more fine root biomass and higher fine root growth in colder than in warmer soil areas. Moreover, colder areas showed higher fine root turnover and thus lower root lifespan than warmer places. We conclude that Pinus cembra balances enhanced fine root mortality in cold soils with higher fine root activity and by maintaining higher fine root biomass, most likely as a response to shortage in soil resource supply. The results from our study highlight the importance of in situ measurements on mature trees to understand the fine root response and carbon allocation pattern to the thermal growth conditions at the alpine treeline.